The monster of Florence - Preston, Douglas J.; Spezi, Mario, 1946- (New York : Grand Central Pub., 2008)
An American writer who moved to Florence works with an Italian journalist to discover the idenity of a local serial killer.
Includes index.
Keywords: Serial murders -- Italy -- Florence -- Case studies